2022
DOI: 10.1177/17479541221122396
|View full text |Cite
|
Sign up to set email alerts
|

Pre- and post-competitive anxiety and match outcome in elite international junior tennis players

Abstract: This study aimed to analyse the impact of match outcome (win or lose) in an elite international tennis competition on pre-competitive anxiety and self-confidence. A cohort of Under-16 elite boys (n = 18), with a mean age of 15.44 (0.616) years and an international competitive experience of 4.44 (1.89) years, which were representing six national teams participated in this cross-sectional study. The assessments took part in a qualifying stage of the International Tennis Federation (ITF) Junior Davis Cup competit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 44 publications
0
5
1
Order By: Relevance
“…Conversely, losing players demonstrated expected increases in anxiety and decreases in self-confidence post-match, potentially due to underperformance and emotional distress. This contrasts with prior research on singles tennis players on official competition (16). Overall, these findings highlight the contrasting impact of victory and defeat, indicating that while winning might not necessarily yield favorable effects, the repercussions of losing could be considerably detrimental to players.…”
Section: Discussioncontrasting
confidence: 96%
See 3 more Smart Citations
“…Conversely, losing players demonstrated expected increases in anxiety and decreases in self-confidence post-match, potentially due to underperformance and emotional distress. This contrasts with prior research on singles tennis players on official competition (16). Overall, these findings highlight the contrasting impact of victory and defeat, indicating that while winning might not necessarily yield favorable effects, the repercussions of losing could be considerably detrimental to players.…”
Section: Discussioncontrasting
confidence: 96%
“…This could be due to the fact that the increase of self-confidence is linked, among other factors, to positive performance results ( 56 ). In this line, Fuentes-García et al ( 16 ) observed higher post-match self-confidence among winning elite junior tennis players compared to losers.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…One of the other possible limits is the sensitivity of the measured constructs. Relationships between the players and the coaches and sports self-confidence (mainly in athletes; see [109,111]) have a rather dynamic character, which can be influenced by a number of phenomena from the internal and external environment. In addition, all the analyzed variables are related to performance in some way, and elite athletes who are performance-oriented could respond in the context of the current sport form.…”
Section: Limits Of Researchmentioning
confidence: 99%